Voltage-Gated Sodium Channels Modulation by Bothutous Schach Scorpion Venom: Detection of sodium blocker fraction on scorpion venom - Akram Aboutorabi; Nima Naderi; Hossein Vatanpour; Hamid Gholami pourbadie; Hossein Zolfagharian (Iranian Journal of Pharmaceutical Sciences, 2016)
Buthotus schach is one of the dangers scorpions in Iran that belong to the Buthidae family. Toxins are existing in venom scorpion, modulate the ion channels by blocking or opening the pore of the channel or by altering the voltage gating and useful as pharmacological tools. In the present study, we investigated the effects of venom and its obtained fractions by gel filtration on electrophysiological properties of magnocellular supraoptic of hypothalamus by using whole cell patch clamp. Our results shown indicated scorpion crude venom and its fraction effect on voltage gated sodium channels. A significant decrease was revealed in amplitude firing, in venom various concentration and some of the venom fractions. Also, a significant increase was shown in half width and rise time 10% to 90% actions potential firing. Previous evidence revealed a change in electrophysiological properties such as amplitude and rise time 10% to 90%, related to voltage gated sodium channels. Sodium channels toxins existed on scorpion venom caused modulate on sodium channels. In order to access bioactive components, six fractions were collected by gel chromatography techniques. After bath application of fractions, F2 and F3 components show the same effects than venom on electrophysiological properties of magnocellular supraoptic.